Analisis Perkembangan Pendidikan Islam di Iran - Tri Yuliani; Iswadi Iswadi; Armizawati Armizawati; Desnawita Desnawita; Desni Yulinda (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research aims to analyze the development of Islamic education in Iran through library research or library research as a research method. Data collection in this study uses the analysis of scientific journals that have been published to see how the development process of Islamic education in Iran and see the differences in Islamic education in Indonesia. This finding produced several differences in the development of Islamic education in Iran and Indonesia. The results of this study can provide an overview of the progress of education in Iran that can be collaborated with the education system and Islamic education curriculum in Indonesia. The results of this study are expected to be useful for the public in the preparation of education curricula in Indonesia in the future